Structural and functional characteristics of the heart before and after CRT in patients with heart failure - Bagdat Akhyt; Roza Kuanyshbekova; Kurmangazy Madaliyev; Aisulu Mussagaliyeva; Kulzida Koshumbayeva; Assel Issabekova; Kuralay Atageldiyeva (National Scientific Medical Center, 2022)
Abstract: The aim of the study was to evaluate the clinical and hemodynamic effects of resynchronization therapy in patients with congestive heart failure. Materials and methods: Seventy-six consecutive patients underwent echocardiography, NYHA classification, 6-minute walk test and clinical assessment scale modified by Mareev, before and after cardiac resynchronization therapy. All had complete left bundle branch block, with a QRS complex duration ≥ 130 ms. and left ventricular ejection fraction ≤ 35%. Also, all patients had received optimal medical therapy for at least 3 months before inclusion to the study. Results: We observed significant increase in left ventricular ejection fraction (35.4±3.7%, p < 0.001, compared with baseline) and decrease in end-systolic volume of the left ventricle (20.2 ±3.0 %, p < 0.001 compared with baseline). Improvement in functional class of congestive heart failure by NYHA classification by > 1 was observed in 68.4% of individuals, in 26.3% of participants demonstrated no change and 5.3% of patients had worsening of CHF symptoms. Conclusions: The response of patients with congestive heart failure to cardiac resynchronization therapy is heterogeneous. The relationship between left ventricular reverse remodeling and the functional class of the congestive heart failure was not significant. Key words: congestive heart failure, cardiac resynchronizing therapy, optimal drug therapy.